Sorption of beryllium in cementitious systems relevant for nuclear waste disposal: Quantitative description and mechanistic understanding. (November 2021) - Çevirim-Papaioannou, N.; Androniuk, I.; Han, S.; Mouheb, N. Ait; Gaboreau, S.; Um, W.; Gaona, X.; Altmaier, M.
Abstract: Beryllium has applications in fission and fusion reactors, and it is present in specific streams of radioactive waste. Accordingly, the environmental mobility of beryllium needs to be assessed in the context of repositories for nuclear waste. Although cement is widely used in these facilities, Be(II) uptake by cementitious materials was not previously investigated and was hence assumed negligible. Sorption experiments were performed under Ar-atmosphere. Ordinary Portland cement, low pH cement, calcium silicate hydrated (C–S–H) phases and the model system TiO2 were investigated. Sorption kinetics, sorption isotherms and distribution ratios (Rd, in kg⋅L −1 ) were determined for these systems. Molecular dynamics were used to characterize the surface processes driving Be(II) uptake. A strong uptake (5 ≤ log Rd ≤ 7) is quantified for all investigated cementitious systems. Linear sorption isotherms are observed over three orders of magnitude in [Be(II)]aq, confirming that the uptake is controlled by sorption processes and that solubility phenomena is not relevant within the investigated conditions. The analogous behaviour observed for cement and C–S–H support that the latter are the main sink of beryllium. The two step sorption kinetics is explained by a fast surface complexation process, followed by the slow incorporation of Be(II) in C–S–H. Molecular dynamics indicate that Be(OH)3 – and Be(OH)4 2− are sorbed to the C–S–H surface through Ca-bridges. This work provides a comprehensive quantitative and mechanistic description of Be(II) uptake by cementitious materials, whose retention properties can be now reliably assessed for a wide range of boundary conditions of relevance in nuclear waste disposal. Highlights: First experimental study investigating beryllium uptake by cementitious materials. Very strong sorption observed. C–S–H confirmed as main sink of beryllium in cement. Uptake process controlled by fast adsorption followed by slow incorporation in C–S–H. MD simulations indicate sorption of Be species to C–S–H surface through Ca-bridges. Reliable assessment of Be retention/mobilization in a repository now feasible.